Influence of larning interest and vocabulary on the writing description of secondary school in Depok - Dwi Septiani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
The purpose of this research: (1) to know the influence of the interaction of learning interest and mastery of the standard vocabulary together to the ability to write the description of the students of SMPN in Depok. (2) to know the effect on the ability to write the description of SMPN students in Depok. (3) to know the influence of standard vocabulary mastery to the ability to write the description of SMPN students in Depok. The research method used is survey method with multiple correlation regression analysis. The sample of the research is the students of class VII: SMPN 1 Depok and SMPN 2 Depok as many as 80 students and take a simple random technique. Data collection was done by direct questionnaire to sample. Data analysis uses descriptive statistics, such as searching for mean (mean), median, mode, standard deviation, and inferential statistics, ie to find simple and double correlation coefficients followed by correlation coefficient significance test with t test. The findings of the researcher indicate that: (1) there is a significant influence of learning interest and mastery of the standard vocabulary simultaneously to the ability to write student description with the acquisition value Fo= 21,909 and Sig.= 0,000 < 0.05; (2) there is a significant influence of learning interest on the ability to write student description with thitung (3,564) > t table (1,99) and Sig. 0.001 < 0.05; (3) there is a significant influence of vocabulary mastery of the learning achievement on the subject of writing description. This is evidenced by the value of thitung (5.909) > t table (1.99) and Sig. 0,000 < 0.05.